SUSTAINABLE FOREST MANAGEMENT IN REPUBLIC OF NORTH MACEDONIA – CONDITIONS AND POSSIBILITIES - Georgievska K.; Hadzi Naumova-Mihajlovska K. (Institute of economics-Skopje, 2022)
Sustainable forest management offers a holistic approach to ensure that forest activities provide social, environmental and economic benefits, balance competitive needs and maintain and develop forest functions now and in the future. In Republic of North Macedonia the planning, management, cultivation, protection and use of forests and forest land as well as other issues of importance on the principle of biological, economic, social and ecological acceptability are regulated by the Law on Forests. Main hypothesis of the paper is that sustainable forest management in the Republic of North Macedonia provides the basic functions of the forest: economic, environmental and protective. Therefore, the purpose of the paper is based on the analysis of the forest management situation in the Republic of North Macedonia to point out the importance and opportunities of sustainable forest management in the country, i.e. that it has a great impact not only on productivity and profits, but also the overall development of the country.
Keywords: forest management, sustainable development, Republic of North Macedonia